2015
DOI: 10.1016/j.maturitas.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medicine treatment for menopausal symptoms in the UK health service: Is a clinical trial warranted?

Abstract: Abstract:Objectives: The aims of this pilot study were to evaluate treatment effects, ascertain safety and formulate best practice Chinese medicine protocols relevant for London women suffering from menopausal symptoms. Study Design:This clinical pilot study employed a case series design within a wider action-based research project. 117 perimenopausal women between 45-55 years of age recruited from the general population were treated for menopausal symptoms by six experienced practitioners of Chinese medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…We however successfully evaluated feasibility as planned and a significant strength of this study is that we collected data prospectively on standardised and individualised multiherb CHMs which were administered according to real-world practice and for 6 months. Safety and adverse events data from our study appear to be consistent with the findings of previous CHM studies in the UK 29 35 36 which suggest that CHMs appear to be safe and overall well tolerated. Our study compared real-world CHM-prescribing approaches for a significant duration of time, whereas the majority of previous PCOS and CHM trials evaluate standardised CHMs for <6 months.…”
Section: Discussionsupporting
confidence: 89%
“…We however successfully evaluated feasibility as planned and a significant strength of this study is that we collected data prospectively on standardised and individualised multiherb CHMs which were administered according to real-world practice and for 6 months. Safety and adverse events data from our study appear to be consistent with the findings of previous CHM studies in the UK 29 35 36 which suggest that CHMs appear to be safe and overall well tolerated. Our study compared real-world CHM-prescribing approaches for a significant duration of time, whereas the majority of previous PCOS and CHM trials evaluate standardised CHMs for <6 months.…”
Section: Discussionsupporting
confidence: 89%
“…Alternative medicine especially traditional oriental medicine called much attention in battle with certain ailments [ 32 ]. Interestingly, herbs are usually very useful in treating disorders that lack obvious pathological alterations such as menopausal syndrome [ 33 , 34 ]. Previously, natural product such as soybean extract is reported to proliferate the vagina of adult rats [ 35 ] and could lower the cancer risk comparing to estrogen treatment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, with respect to evaluating effectiveness of the herbal treatment there are significant limitations of the study design (pre-post design with no control group), and these have already been described. 1 However, the lack of control group is irrelevant for the research question being addressed in the current paper. Table 5 traces the patterns of herb usage listed in Table 2 to commonly used Chinese herbal medicine formulas described in contemporary formularies, 28 It also compares them to a list of the most commonly used Chinese medicine formulas for treating menopausal symptoms that we published in an exhaustive literature review of the field.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The rationale, design and outcomes of the study have already been reported elsewhere. 1 They indicate that Chinese medicine is both safe and potentially effective in treating menopausal symptoms, warranting further investigation by means of a pragmatic randomised controlled trial (RCT). The analysis of prescribing patterns presented in this paper is intended to inform the development of good practice guidelines for such a trial.…”
Section: Introductionmentioning
confidence: 99%